Luís Adão da Fonseca: from a pioneering to a mature approach in the research on military orders in Portugal - Costa,Paula Pinto (2020)
Abstract In the course of his extensive research work, Luís Adão da Fonseca adopted a pioneering and innovative approach to the study of the military orders in Portugal, making a decisive contribution to the evolution of this thematic field in recent years. Over almost four decades, he opened up a series of promising questions and perspectives, becoming the mentor of a particular school and a major reference in this scientific area.